Community-Based Study of Abortion Complications and Care Sought by Rural Tribal Women of an Extremely Low Resource Setting - Chhabra, Shakuntala; Suman, Akanksha (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: Knowing about complications, care sought by women is essential for understanding the risks, services, programs, and policies for abortion care. This study aimed to know the magnitude of abortion complications and to define the care sought by rural tribal women. STUDY DESIGN: Rural community-based cross-sectional study was carried out in villages near Sewagram Wardha and Melghat, Amravati, Maharashtra, India. RESULTS: Spontaneous abortions rate was 3.30% in villages around Sewagram and 0.32% in villages of Melghat. The reported complications rate for induced abortions was 1% in Sewagram villages and 0.1%in Melghat villages. In Sewagram villages, among 24 (4.3%) women who had complications with spontaneous abortions, the reported complications were: vaginal bleeding in 33.3% (1.4% of all spontaneous abortions), abdominal pain in 33.3%, weakness in 29.16% (1.2% all spontaneous abortions), backache in16.6% (0.7%of spontaneous abortions), fever in 12.5%(0.5% of spontaneous abortions), excessive vaginal discharge in 8.33% (0.3% of spontaneous abortions), and other complications in 8.33% (0.36% of spontaneous abortions) women. Among 7 women (3.9% of all 177), who reported complications after induced abortions, 57.1% (2.2% of all induced abortions) reported, vaginal bleeding and 28.5% (1.1% of induced abortions) reported abdominal pain. In Melghat villages only 4 women reported complications with spontaneous abortions (0.32% spontaneous abortions): two (0.16% spontaneous abortions) reported abdominal pain, one (0.08% spontaneous abortions) reported vaginal bleeding, and one (0.08% of spontaneous abortions) reported backache. In villages of Melghat 2 women (3.7%) out of 27 induced abortions cases had complications: one had vaginal bleeding, discharge, pain, weakness, another only vaginal bleeding. In villages of Melghat 2 of the total 6 sought health facility care, however, no one reported to specialists despite complications. Nevertheless, there was neither abortion-related mortality nor near-miss morbidity or severe morbidity during the same duration. CONCLUSION: Research is needed about traditional therapies, reverse pharmacology, socio-behavioral issues in addition to creating awareness in women about abortion complications, long-term squeal, and the necessity of care-seeking.